Artificial Intelligence in English Language Teaching: Fostering Joint Enterprise in Online Communities - Floris, Flora Debora; Widiati, Utami; Renandya, Willy Ardian; Basthomi, Yazid (JEES (Journal of English Educators Society), 2024)
This paper examines the role of Joint Enterprise within Virtual Communities of Practice (VCoP) in the realm of English Language Teaching (ELT), particularly in relation to the integration of Artificial Intelligence (AI) tools. The study focuses on the discussions in five open Facebook groups, to explore how teachers collectively navigate the application of AI technologies. The discussions reflect an effort among teachers to not only integrate AI tools into their teaching practices but also to ensure these tools are used ethically and effectively, balancing technological advancements with pedagogical soundness. The findings of the study underscore the critical role of Joint Enterprise in fostering a community that is responsive to evolving educational technologies. HIGHLIGHTS: The study revealed that English teachers in the selected Facebook groups engaging collaboratively on Artificial Intelligence (AI) tools, discussing their integration, acceptance, and application in teaching practices. The teachers also expressed concerns about AI in English Language Teaching (ELT), focusing on ethical use, over-reliance risks, and the importance of teacher involvement, highlighting a collective effort to address these AI-related challenges. Reflecting on the concept of Joint Enterprise within Virtual Communities of Practice (VCoP), the findings illustrate the dynamic roles assumed by community members, encompassing information sharers, knowledge seekers, critics, and learners.